Assessing the responses of vegetation to meteorological drought and its influencing factors with partial wavelet coherence analysis. (1st June 2022) - Zhou, Zhaoqiang; Liu, Suning; Ding, Yibo; Fu, Qiang; Wang, Yao; Cai, Hejiang; Shi, Haiyun
Abstract: The increase in drought frequency in recent years is considered as an important factor affecting vegetation diversity. Understanding the responses of vegetation dynamics to drought is helpful to reveal the behavioral mechanisms of terrestrial ecosystems and propose effective drought control measures. In this study, long time series of Normalized Difference Vegetation Index (NDVI) and Solar-induced chlorophyll fluorescence (SIF) were used to analyze the vegetation dynamics in the Pearl River Basin (PRB). The relationship between vegetation and meteorological drought was evaluated, and the corresponding differences among different vegetation types were revealed. Based on an improved partial wavelet coherence (PWC) analysis, the influences of teleconnection factors (i.e., large-scale climate patterns and solar activity) on the response relationship between meteorological drought and vegetation were quantitatively analyzed to determine the roles of factors. The results indicate that (a) vegetation in the PRB showed an increasing trend from 2001 to 2019, and the SIF increased more than that of NDVI; (b) the vegetation response time (VRT) based on NDVI (VRTN ) was typically 4–6 months, while the VRT based on SIF (VRTS ) was typically 2–4 months. The VRT was shortest in the woody savannas and longest in the evergreen broadleaf forests. (c) The relationship between the SIF and meteorological drought was more significant than that between the NDVI and meteorological drought. (d) There was a significant positive correlation between meteorological drought and vegetation in the period of 8–20 years. The El Niño Southern Oscillation (ENSO), Pacific Decadal Oscillation (PDO) and sunspots were important driving factors affecting the response relationship between drought and vegetation. Specifically, the PDO had the greatest impacts among these factors. Highlights: PWC was introduced to study the responses of vegetation to drought for the first time. Herbaceous plants responded faster than woody plants to drought. The vegetation response time based on SIF was less than that based on NDVI. The ENSO, PDO and sunspots were the main factors affecting the response relationship.